2016
DOI: 10.1042/cs20160328
|View full text |Cite
|
Sign up to set email alerts
|

Serelaxin improves the therapeutic efficacy of RXFP1-expressing human amnion epithelial cells in experimental allergic airway disease

Abstract: Current asthma therapies primarily target airway inflammation (AI) and suppress episodes of airway hyperresponsiveness (AHR) but fail to treat airway remodelling (AWR), which can develop independently of AI and contribute to irreversible airway obstruction. The present study compared the anti-remodelling and therapeutic efficacy of human bone marrow-derived mesenchymal stem cells (MSCs) to that of human amnion epithelial stem cells (AECs) in the setting of chronic allergic airways disease (AAD), in the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 57 publications
3
28
0
Order By: Relevance
“…The key finding of this study was that MCA‐MSCs, when given intranasally, reversed fibrosis and reverted AHR to levels measured in uninjured mice. These findings are consistent with previous studies that show that therapies that were able to abrogate AWR, specifically aberrant airway collagen deposition and TGF‐β1 levels, were seen to reverse AHR (15, 28, 32, 41). AHR is driven by airway obstruction, which can be caused by mucus plugging from goblet cell metaplasia (50) and by epithelial thickening (38).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The key finding of this study was that MCA‐MSCs, when given intranasally, reversed fibrosis and reverted AHR to levels measured in uninjured mice. These findings are consistent with previous studies that show that therapies that were able to abrogate AWR, specifically aberrant airway collagen deposition and TGF‐β1 levels, were seen to reverse AHR (15, 28, 32, 41). AHR is driven by airway obstruction, which can be caused by mucus plugging from goblet cell metaplasia (50) and by epithelial thickening (38).…”
Section: Resultssupporting
confidence: 92%
“…Twenty‐four hours after the establishment of chronic AAD (on d 64), subgroups of Ova‐ or Sal‐sensitized/challenged mice ( n = 8 mice/group) underwent IV or IN administration of MCA‐MSCs. In all cases, a 14‐d treatment period (from d 64 to 77) was chosen to replicate the time frame used to evaluate the intranasally delivered effects of other stem cells, such as human bone marrow–derived (stromal) MSCs (15, 28) and human amnion epithelial cells (28), in the Ova‐induced chronic model of AAD.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, hAEC reportedly exerted immunomodulatory effects in the developing lungs such that delivery of hAECs attenuated pulmonary inflammation in sheep fetuses that were challenged with lipopolysaccharide . In a murine model of hyperoxia induced neonatal lung injury, hAEC also reversed alveolar simplification . When media conditioned by hCMSC from preterm babies were cocultured with fetal rat lungs (E14.5–15.5), ex vivo lung growth was markedly accelerated after 72‐hour culture .…”
Section: Preclinical Applicationsmentioning
confidence: 97%
“…Recent studies also showed efficacy of intranasal relaxin administration in allergic airway disease and cigarette smoke induced lung damage (Royce et al, 2014; Pini et al, 2016). In an exciting development, relaxin and bone marrow-derived mesenchymal stem cells or amnionic epithelial stem cells were found to be synergistic in the treatment of established airway disease (Royce et al, 2015, 2016). The mechanism for this effect is currently under investigation, but appears to be related to the matrix remodeling and anti-TGFβ effects of relaxin promoting a favorable environment for the establishment of stem cell residency in the damaged tissue (Samuel et al, 2016b).…”
Section: Relaxinmentioning
confidence: 99%